The Islamic Shrines in the Haifa District, Occupied Palestine - Al-Houdalieh, Salah Hussein (Jordan Journal for History and Archaeology, 2025)
Throughout history, all human societies have developed unique religious beliefs that serve as the basis for their rituals and religious practices. These practices are aimed at establishing a connection with either multiple deities, as evident in polytheistic religions, or a singular deity, as observed in monotheistic religions. The Palestinian Arab community stands as a notable example of a group whose cultural context has embraced prevalent religious expressions. This is exemplified by their construction of shrines and their regular visits to them, which reflect their strong belief that the custodians of these shrines receive divine blessings generously bestowed upon individuals. The main objective of this research is to examine the Islamic shrines situated in the Haifa District. The findings of this investigation reveal a total of 105 shrines in this specific region. These shrines are categorized into five distinct types: architectural shrines, graves, caves, trees, water springs, and stone circles. Unfortunately, a significant number of these shrines have been subjected to destruction, leading to the loss of their unique characteristics. This study primarily relies on a review of relevant literature and field visits to the aforementioned shrines. The goals of this study are to evaluate the current physical condition of these shrines and shed light on the infringements by Israeli authorities.